Modulation of Heat Shock Protein Expression in Alveolar Adenocarcinoma Cells through Gold Nanoparticles and Cisplatin Treatment - Bashiru Ibrahim; Taiwo Hassan Akere; Swaroop Chakraborty; Eugenia Valsami-Jones; Hanene Ali-Boucetta (MDPI AG, 2024)
Heat-shock proteins (HSPs) are stress-responsive molecules belonging to the family of evolutionary molecular chaperones known to be crucial in many cancer types, including human alveolar adenocarcinoma cells (A549). These proteins are highly overexpressed in cancers to support their ability to accommodate imbalances in cell signalling, DNA alterations, proteins, and energy metabolism associated with oncogenesis. The current study evaluated the effects of gold nanoparticles (AuNPs) combined with cisplatin (CDDP) on molecular chaperone HSPs in A549 cells. It was found that AuNPs:CDDP decreased the percentage of cell viability (38.5%) measured using the modified lactated dehydrogenase (mLDH) and 3-[4,5-dimethylthiazole-2-yl]-2,5-diphenyltetrazolium bromide (MTT) assays. AuNPs:CDDP exposure caused a significant (p < 0.05) increase in reactive oxygen species (ROS) generation by 1.81-fold, apoptosis induction, and a decrease in the mitochondrial membrane potential (MMP) compared to AuNPs or CDDP alone. Similarly, exposure to the AuNPs:CDDP combination had pronounced cytotoxic effects on the expression of HSPs and PI3K/AKT/mTOR, as well as apoptosis-related proteins. The results demonstrate that the combination of AuNPs with CDDP might enhance the anticancer efficacy of CDDP.